GAMBARAN KUALITAS HIDUP PENDERITA PSORIASIS DIKOMUNITAS PSOBAT JAWA TENGAH - Susanti, Ratna; Adi, Mateus Sakundarno; Susanto, Henry Setyawan; Sutiningsih, Dwi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Psoriasis is a chronic skin inflammatory caused physical appearance disorders that can reduced the quality of life of patients. The quality of life of patients with psoriasis in the community had not been studied. The purpose of this study was to describe the quality of life of patients with psoriasis in the Central Java Psobat community using Dermatology Life Quality Index (DLQI) questionnaires. This study was a descriptive study with cross sectional study approach. Data were obtained from members of Central Java Psobat community on 2019 report. Using total sampling method was applied to get 39 patients with psoriasis. The results of this research show that the members of the Central Java Psobat Community had average age of 33 years. The respondents had average duration of illness was 7,5 years. The proportion of patients with less quality of life were greater in respondents with stress (69.2%) and obesity (60%). the proportion of patients with bad quality of life was greater in respondents with less social support (47.6%). Conclusion The proportion of patients with less quality of life is greater than the proportion of patients with good and bad quality of life. According the result of this study suggest that the Central Java Psobat community to increase activities in the community by holding regular seminars or community meetings.